Drosophila melanogaster as a Model Organism to Study Lithium and Boron Bioactivity - Katharina Jans (MDPI AG, 2021)
The fruit fly Drosophila melanogaster has become a valuable model organism in nutritional science, which can be applied to elucidate the physiology and the biological function of nutrients, including trace elements. Importantly, the application of chemically defined diets enables the supply of trace elements for nutritional studies under highly standardized dietary conditions. Thus, the bioavailability and bioactivity of trace elements can be systematically monitored in D. melanogaster. Numerous studies have already revealed that central aspects of trace element homeostasis are evolutionary conserved among the fruit fly and mammalian species. While there is sufficient evidence of vital functions of boron (B) in plants, there is also evidence regarding its bioactivity in animals and humans. Lithium (Li) is well known for its role in the therapy of bipolar disorder. Furthermore, recent findings suggest beneficial effects of Li regarding neuroprotection as well as healthy ageing and longevity in D. melanogaster. However, no specific essential function in the animal kingdom has been found for either of the two elements so far. Here, we summarize the current knowledge of Li and B bioactivity in D. melanogaster in the context of health and disease prevention.